Mental Health Children during Pandemic Covid 19: A Bibliometric Study - Nunung Siti Sukaesih; Hikmat Pramajati; Sri Wulan Lindasari; Emi Lindayani; Dewi Dolifah; Popi Sopiah (Universitas Padjadjaran, 2021)
The coronavirus 2019 (Covid- 19) pandemic offers incredible challenges to child and adolescent health because the school closure and the impracticability of activities outside the house have been challenging for parents. When schools are closed, they lose an anchor in life, and their symptoms could relapse; these unstoppable circumstances, which are beyond average experience, are primary to stress, anxiety, and a feeling of helplessness in all. This research aimed at identifying, analysing, and examining children's mental health during pandemic articles published in several reputable international journals issued in the 2019-2020 timeframe, which was led using bibliometric studies. This research hires a bibliographic study using systematic and explicit mapping methods. The research was conducted using a 4-stages systematic mapping method: (1) searching for articles using the Publish or Perish application in the Scopus database, (2) classifying the articles for the bibliometric analysis, (3) checking and completing the metadata of those articles, and (4) conducting bibliometric analysis using VOSviewer application. The bibliometric analysis produced four findings, as follows: (1) the trend of mental health children’s publications 2019-2020; (2) the ten most contributive journals has published; (3) the ten most cited articles has produced 170 citations; (4) the five highest order of author keywords most widely used in mental health children’s articles were mental health, children, human, school, and covid- 19. Children's mental health can be concluded as the term of research is currently popular among researchers.